Herpes neolabialis: herpes simplex virus type 1 infection of the neolabia in a transgender woman. (July 2017) - Elfering, Lian; van der Sluis, Wouter B; Mermans, Joline F; Buncamper, Marlon E
A 24-year-old transgender woman consulted our outpatient clinic with a painful, itchy and red left labia. She underwent a penile inversion vaginoplasty 18 months before presentation. At physical examination of the left labia, erythema, edema and herpetic vesicles with ulceration were observed. A vesicle fluid swab was obtained and the presence of herpes simplex virus type 1 (HSV-1) was detected by PCR assay. Treatment consisted of oral valaciclovir (500 mg twice daily) for a total of five days.Topically-applied lidocaine cream (3%) was used for pain management. Treatment gave symptom relief in five days. At physical examination 14 days after symptom onset, there were no signs of active infection. To our knowledge, this is the first case report of HSV-1 infection of the neolabia in a transgender woman.